Faktor-Faktor yang Berhubungan dengan Perilaku Ibu Balita Menimbang Anaknya ke Posyandu - Achmad Djamil (Politeknik Kesehatan Tanjung Karang, 2017)
This study was to determine the factors associated with the behavior of mothers to weigh their children to health centers in the region of IHCWay Panji District of South Lampung Regency 2016.This research is a quantitative research with cross sectional approach.The results showed no correlation between knowledge (p-value=0.027), there is a relationship attitude (p-value=0.039), there was no distance relationship posyandu (p-value=0.027), there is a correlation with health (p-value=0.009), there is a relationship of family support (p-value=0.010), there was no relationship of friend support (p-value=0.067). No relationship support of community leaders (p-value=0.013), and there is a relationship of support cadre (p-value=0.010) with the behavior of his mother weighed into the Posyandu.Conclusion: The results showed any correlation between knowledge (p-value=0.027), there is a relationship attitude (p value = 0.039), there is a correlation with health (p-value=0.009), there is a relationship of family support (p value = 0.010), and there is a relationship of support cadre (p-value=0.010) with the behavior of his mother weighed into the Posyandu.